Parenting practices and oral health behaviors of children in rural Egypt: gender differences in a household survey - Maha El Tantawi; Nourhan M. Aly; Sara Atteya; Enas Abdellatif; Randa Yassin (BMC, 2022)
Abstract Background Parenting practices influence children's health and development. The current study aimed at assessing gender differences in children's perception of the parenting practices of both parents, and in the association between children's oral health behaviors and parenting practices. Methods A cross-sectional household survey of 6-12 year old children was conducted in a rural area in Northwestern Egypt in 2019. Clinical examination assessed caries and gingivitis. The Alabama Parenting Questionnaire assessed parenting practices in five domains (positive parenting, involvement, inconsistent disciplining, poor monitoring and corporal punishment) and the World Health Organization questionnaire assessed oral health behaviors including sugar consumption and daily toothbrushing. Sugar consumption was the dependent variable in linear regression and daily toothbrushing was the dependent variable in logistic regression. Parenting practices were the explanatory variables adjusting for confounders. Effect modification by child gender was assessed. Results The response rate was 94.1% (n = 433), mean age = 9.9 years, 44.1% boys, 17.8% with daily toothbrushing and mean sugar consumption score = 3.4/8. Girls perceived more mothers' positive parenting than boys (mean = 14.15 and 13.46) and boys perceived more poor monitoring and corporal punishment. Boys and girls differed in the association between sugar consumption and fathers' inconsistent disciplining, poor monitoring (P = 0.004 and 0.02) and mothers' corporal punishment (P = 0.02), and also daily toothbrushing and mothers' involvement, positive parenting (P = 0.05 and 0.02), fathers' positive parenting (P = 0.02), mothers' inconsistent discipling and poor monitoring (P = 0.01 and 0.04). Conclusions There were differences between boys and girls in perceiving mothers' and fathers' parenting practices and in the association between these parenting practices and toothbrushing and sugar consumption.